GABA-A and NMDA receptor subunit mRNA expression is altered in the caudate but not the putamen of the postmortem brains of alcoholics - Bhandage, Amol K.; Jin, Zhe; Bazov, Igor; Kononenko, Olga; Bakalkin, Georgy; Korpi, Esa R.; Birnir, Bryndis (Frontiers in Cellular Neuroscience, 2014)
Chronic consumption of alcohol by humans has been shown to lead to impairment of executive and cognitive functions. Here we have studied the changes that take place in the dorsal striatum in post-mortem brains of alcoholics and normal controls. The results show a significant change in the expression of both the excitatory ionotropic glutamate receptor and the inhibitory GABA-A receptor subunit genes in the caudate but not the putamen of the striatum. The mRNA levels in the caudate encoding the glutamate receptor subunit GluN2A and the GABA-A receptor subunits δ, ε and ρ2 were significantly decreased whereas the GluD1, GluD2 and the GABA-A γ1 mRNA levels were significantly increased in the alcoholics as compared to controls. Interestingly in controls, 11 glutamate and 5 GABA-A receptor genes were more prominently (fold-increase varied from 1.24 to 2.91) expressed in the caudate than the putamen. We have previously shown in post-mortem samples from alcoholics that the expression level of glutamate and GABA-A receptor genes in the dorsal-lateral prefrontal cortex is similar to that of normal controls (Jin et al., 2011a;Jin et al., 2014b). This is in contrast to the present study. As the caudate is vital for automatic thinking, the results indicate that the balance between voluntary and automatic control of behaviours is altered in alcoholics. Our results suggest that there may be diminished executive control on goal-directed alcohol-seeking behaviour and, rather, a shift to greater striatal control over behaviours that may be critical in the progress of becoming an alcoholic.